Halal entrepreneurship: concept and business opportunities - Abdullah, Moha Asri; Azam, Siddique (IntechOpen, 2021)
The concept of entrepreneurship is not something new in Islam as it can be observed from the history as a noble profession practiced by the Prophet (PBUH) and His companions. However, in recent times, scholars of the Islamic economy have introduced a new term, “Halal entrepreneurship” or “Halalpreneurship” to define and differentiate entrepreneurs in the Halal industry from the conventional entrepreneurs. The integration of Islamic values reshapes the entrepreneurs in the Halal industry through certain features that justify using the term Halalpreneurs and Halalpreneurship. However, a limited number of research papers have attempted to define Halalpreneurship. In this context, this chapter aims to achieve two main objectives. Firstly, to provide a comprehensive overview of Halal entrepreneurship (Halalpreneurship) by identifying its salient features that differentiates from entrepreneurs. Such understanding and knowledge will help someone to identify his/her role as Halalpreneur in the Halal industry. Secondly, to explore the business opportunities in different sectors of the global halal industry for the Halalpreneurs to tap. To achieve the objectives, the chapter adopts the methodology of content analysis by reviewing research papers, books, journals, and articles from different secondary sources.